Analysis of Professional Ethics Violations At Anderson and Public Accounting Firm Indonesia - Syamsiyatur Robi’ah; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Based on the official announcement from the Financial Services Authority (OJK) as the regulatory body, the Public Accounting Firm Anderson and Partners was issued an administrative sanction in the form of a one-year suspension of their registration from the date the letter was issued. The ethical violations committed by Public Accountant Anderson Subri from Anderson and Partners highlight the importance of applying professional ethics in the audit process of financial statements. This case also demonstrates the critical need for compliance with OJK regulations for registered Public Accountants and Public Accounting Firms. One of the key violations involved non-compliance with regulations regarding the conformity of transactions with applicable laws, which could lead to potential errors in the presentation of financial information. Ethics serve as a moral guide that ensures external auditors perform their duties in accordance with professional standards. This case underscores that adherence to professional codes of ethics is a crucial aspect for public accountants